ANALISIS TIPOLOGI ARSITEKTUR AKOMODASI WISATA BERBASIS MASYARAKAT (AWBM) DI DESA WISATA BONGKASA PERTIWI, KAB. BADUNG, BALI - Prabawa, Made Suryanatha (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2023)
This study discusses the typology of community-based tourist accommodation (AWBM) in the Bongkasa Pertiwi Village area. Architectural typology is a scientific focus that is used to analyze data related to AWBM found in the field. The purpose of this study is to find the AWBM typology in Bongkasa Pertiwi Village and find the reasons behind the presence of such an AWBM architectural typology in Bongkasa Pertiwi Village. The research method used is a qualitative-descriptive approach with typological analysis methods and zigzag process. The results of the study indicate that the typology of AWBM in Bongkasa Pertiwi Village is in the Balinese Modern Building Style, Compiling Materials (Concrete, Paint, Wooden Horses, Clay Tiles), AWBM buildings with the type of 1st floor building, and have a basic shape of Square or Square geometry. Long. This typology can be created as a result of adaptation actions of land / yard architecture carried out by villagers with the aim of capturing opportunities to increase welfare from the presence of tourists to the village.